The effect of replacing sedentary behavior with different intensities of physical activity on depression and anxiety in Chinese university students: an isotemporal substitution model - Yulan Zhou; Zan Huang; Yanjie Liu; Dongao Liu (BMC, 2024)
Abstract Background Previous research has suggested that engaging in regular physical activity (PA) can help to reduce symptoms of depression and anxiety in university students. However, there is a lack of evidence regarding the impact of reducing sedentary behavior (SB) and increasing light-intensity PA (LPA) on these symptoms. This study aims to address this gap by using isotemporal substitution (IS) models to explore how substituting SB with LPA or moderate-to-vigorous PA (MVPA) affects depression and anxiety symptoms among university students. Methods The study recruited 318 university students with a mean age of 21.13 years. Accelerometers were used to objectively measure the time spent on SB, LPA, and MVPA, while depression and anxiety symptoms were assessed using the Center for Epidemiologic Studies Depression Scale (CES-D) and the Self-rating Anxiety Scale (SAS). IS models using multivariable linear regression were employed to estimate the associations between different behaviors and depression and anxiety symptoms when 30 min of one behavior was substituted with another. Results In the single-activity model, less SB (β = 0.321, 95% CI: 0.089, 1.297) and more MVPA (β = −0.142, 95% CI: −1.496, − 0.071) were found to be significantly and negatively associated with depression scores, while less SB (β = 0.343, 95% CI: 0.057, 1.014), LPA (β = 0.132, 95% CI: 0.049, 1.023), and more MVPA (β = −0.077, 95% CI: −1.446, − 0.052) were significantly and negatively correlated with anxiety scores. The IS analysis revealed that substituting 30 min of SB with LPA (β = −0.202, 95% CI: −1.371, − 0.146) or MVPA (β = −0.308, 95% CI: −0.970, − 0.073) was associated with improvements in depressive symptoms. Substituting 30 min of SB with MVPA (β = −0.147, 95% CI: −1.863, − 0.034) was associated with reduced anxiety symptoms. Conclusion Replacing 30 min of SB with MVPA may alleviate depression and anxiety symptoms in university students. Further research is needed to explore the long-term effects of PA interventions on the mental health disorders of this population.